Trade Wars and Protectionism in International Relations - Asghar, Muhammad Muzammil; Hussain, Saddam (Journal of Global Social Transformation, 2025)
Protectionism and trade wars have become the new issues of the modern international relations, disputing the liberal economic order that prevails in international trade since the mid-twentieth century. Although classical theories of trade argue that free trade and comparative advantage are best practices, tariffs, quotas, subsidies, and non-tariff barriers are becoming popular practices among many states as a way of defending local industries and national interests. This paper will investigate the causes, dynamics and effects of trade wars and protectionist policies in the world system. The paper discusses the role of economic nationalism, geopolitical competition, and domestic political pressures in shaping the action of a state based on the understanding of realist, liberal and dependency views. This is especially so on the recent trade disputes between the United States and China, and the role of the World Trade Organization in settling disputes. The analysis concludes that, even though protectionist policies can provide immediate political and economic benefits, they tend to destabilize the global supply chains and decrease economic growth and also escalate diplomatic tensions. Lastly, sustainable international cooperation would require change in institutions, moderation on the economy and rebirth of commitment to multilateralism.